Sternal fracture due to low-energy trauma with surgical treatment: a case report - Serna Trejos, Juan Santiago (2025)
Sternal fractures are rare and typically associated with high-energy trauma. This report describes the case of a 25-year-old male who presented with neck pain and swelling following a motorcycle accident. Computed tomography revealed an oblique fracture of the sternal manubrium with minimal displacement. Due to difficulties in pain management, surgical intervention was performed, involving fracture fixation with plates and screws. The procedure was successful and uneventful, with adequate postoperative pain control and early discharge. Although conservative management is the standard approach for sternal fractures, surgical intervention may be necessary to stabilize the fracture and improve respiratory mechanics, thereby preventing complications such as pseudoarthrosis. In this case, early surgery enabled a rapid and effective recovery. Current evidence supports plate and screw osteosynthesis as a safe and effective option in selected cases with poor pain control and displaced fractures.